2017
DOI: 10.1038/srep45672
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Enhanced Inference in Markov Logic Networks

Abstract: Markov logic networks (MLNs) reconcile two opposing schools in machine learning and artificial intelligence: causal networks, which account for uncertainty extremely well, and first-order logic, which allows for formal deduction. An MLN is essentially a first-order logic template to generate Markov networks. Inference in MLNs is probabilistic and it is often performed by approximate methods such as Markov chain Monte Carlo (MCMC) Gibbs sampling. An MLN has many regular, symmetric structures that can be exploit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 53 publications
0
14
0
2
Order By: Relevance
“…This possibility is also sure to inspire novel QML ideas. Moving on from BMs, in recent work (Wittek and Gogolin, 2017), the authors have also shown how suitable annealing architectures may be useful to speed-up the performing of probabilistic inference in so-called Markov logic networks 108 . This task involves the estimation of partition functions of arising from statistical models, concretely Markov random fields, which include the Ising model as a special case.…”
Section: Speed-up Via Adiabatic Optimizationmentioning
confidence: 99%
“…This possibility is also sure to inspire novel QML ideas. Moving on from BMs, in recent work (Wittek and Gogolin, 2017), the authors have also shown how suitable annealing architectures may be useful to speed-up the performing of probabilistic inference in so-called Markov logic networks 108 . This task involves the estimation of partition functions of arising from statistical models, concretely Markov random fields, which include the Ising model as a special case.…”
Section: Speed-up Via Adiabatic Optimizationmentioning
confidence: 99%
“…This implementation has double the resource requirements of the first architecture but has the benefit of improvement in execution time. The time complexity is determined as in (20) and the space complexity is given by (21).…”
Section: Cmac Configurationsmentioning
confidence: 99%
“…An experimental realization of a quantum computing silicon chip was fabricated in the work of Qiang et al 18 In contrast to other realizations, this quantum chip does not use product of unitary operation architecture as proposed in the work of Benioff, 1 it employed the linear combinations of unitary (LCU) operations architecture, proposed in the work of Gui-Lu. 19 The LCU has found extensive applications in quantum algorithms recently, as reviewed in the work of Shao et al, 20 extending to quantum machine learning, 21 secure multiparty computing, 22 and passive error correction. 23 Despite having operational quantum hardware, there are critical problems and challenges 24 in these systems that need to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…В [60] рассмотрены марковские логические сети (MLNs), объединяющие две противоположные школы в машинном обучении и искусственном интеллекте: причинно-следственные сети, которые очень хорошо учитывают неопределенность, и логику первого порядка, которая допускает формальные выводы. MLN -это, по сути, логический шаблон первого порядка для создания сетей Маркова.…”
Section: квантовые нейронные сети и системы машинного обучения сущесunclassified
“…MLN имеет множество регулярных симметричных структур, которые разумно использовать и на уровне первого порядка, и в генерируемой сети Маркова. Различными способами проанализированы созданные графовые структуры и определено, в какой степени квантовые протоколы могут использоваться для ускорения выборки Гиббса с помощью схем подготовки и измерения состояния [60]. На основе анализа различных подходов, оценки их преимуществ, теоретических ограничений, возможностей реализации сделан также вывод, что прямое применение полученного результата приводит к экспоненциальному ускорению по сравнению с классическими эвристиками, что подтверждает их потенциальную полезность для применения в машинном обучении.…”
Section: квантовые нейронные сети и системы машинного обучения сущесunclassified